Novel design measures for optimizing the yearlong performance of a concentrating solar thermal power plant using thermal storage and a dry-cooled supercritical CO2 power block. (15th July 2020) - Monjurul Ehsan, M.; Guan, Zhiqiang; Gurgenci, Hal; Klimenko, Alexander
Highlights: Dynamic response of dry cooled supercritical CO2 cycle coupled with solar tower. Usage of additional bypass prior to cooling tower to prevent cycle overcooling. Working mechanism of thermal energy storage with fluctuating ambient temperature. Abstract: Owing to water deficit and environmental concerns, the compatibility of dry cooling technology with supercritical CO2 (sCO2 ) power cycle in concentrated solar power (CSP) offers superior performance even at extreme climate temperatures. The CSP plant performance is expressively dominant by the erratic attributes of solar insolation and varying ambient temperature. In the present work, the dynamic attributes of the dry cooled sCO2 recompression cycle coupled with the central receiver is presented in terms of net power generation at different climate conditions. The supplementary bypass arrangement prior to the dry cooling tower ensures the system operating at the design point compressor inlet temperature in the occasion of low ambient temperatures. Solar tower plant with molten salt thermal energy storage is used to supply dispatchable electricity during nighttime. Based on the annual climate temperature profile, two sets of ambient air temperatures are selected for the cooling system design. This requires the rectification of two sets of design point main compressor inlet temperature/tower exit temperature at optimum turbine exhaust pressure in advance of the integration and design of the dry cooling tower. The key parameters of the solar system (cold tank temperature and molten salt split ratio) and power block (MCIT, pressure ratio, cycle mass, and bypass fraction) are optimized to maximize the power generation at any circumstances. The required height of the tower is 59 m and 67 m at two design points. The average net power using the minimum climate temperature is 23.71 MW and 24.09 MW respectively, whereas using the maximum climate temperature the values are 23.06 MW and 23.45 MW. The dynamic response from the system when the thermal energy storage operates during nighttime using additional bypass is demonstrated under the fluctuation of air temperature. The year-round plant performance as well as the dynamic response from the cooling tower of both cases are assessed with the historical air temperature data.